1990
DOI: 10.1161/01.hyp.15.3.267
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine kinetics and activation of blood platelets in patients with essential hypertension.

Abstract: To investigate possible alterations in 5-hydroxytryptamine (5HT) kinetics and sensitivity of blood platelets in patients with essential hypertension, 45 essential hypertensive patients and 45 normotensive healthy subjects matched in pairs for age, sex, and smoking status were compared. There were 18 women and 27 men in each group, ranging from 30 to 73 years of age. Results of essential hypertensive patients differed in several ways from those of normotensive subjects. In essential hypertensive patients, maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…On the other hand, 5HT content in platelets of normotensives correlates with platelet count. This may indicate that 5HT uptake in viva in normotensives is much lower than Vma x (VNT ,< Vmax) , whereas it may be fully saturated in hypertensives (VHT ~ Vm~), reflecting significantly higher 5HT plasma concentrations in viva in hypertensives than in normotensives [7]. The defect in platelet 5HT uptake, i.e., the reduced Vm~ may lead to a critical increase in 5HT plasma concentrations locally and, consequently, to a higher stimulation by 5HT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, 5HT content in platelets of normotensives correlates with platelet count. This may indicate that 5HT uptake in viva in normotensives is much lower than Vma x (VNT ,< Vmax) , whereas it may be fully saturated in hypertensives (VHT ~ Vm~), reflecting significantly higher 5HT plasma concentrations in viva in hypertensives than in normotensives [7]. The defect in platelet 5HT uptake, i.e., the reduced Vm~ may lead to a critical increase in 5HT plasma concentrations locally and, consequently, to a higher stimulation by 5HT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that maximal velocity of 5HT uptake (Vm~) decreases in patients with essential hypertension [3][4][5][6][7] and that the reduced uptake may lead to higher periplatelet 5HT concentrations, especially in older hypertensive men [7]. All these changes in 5HT kinetics may affect platelet sensitivity to 5HT [7]. Consequently, the aim of the present study was to define the clinical significance of the impaired 5HT uptake and platelet activation in patients with essential hypertension.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…However, many reports showed that plasma 5-HT concentrations and arterial 5-HT receptors are changed in hypertension. In essential hypertensive humans 19 and cyclosporine-induced hypertensive rats, 20 reduced levels of platelet 5-HT and increased plasma 5-HT concentration were measured. Consistent with these reports, unpublished work from our laboratory determined that the DOCA-salt rat platelet 5-HT was reduced (ng/mL of whole blood, SHAM (D) ϭ215.6Ϯ35.4 and DOCAϭ150.4Ϯ 36.7), whereas free-circulating 5-HT concentration was increased (ng/mL whole blood, SHAM (D) ϭ5.82Ϯ1.14 and DOCAϭ28.1Ϯ11.1).…”
Section: Basal 5-ht Concentration Was Reduced In Aorta Of Doca-salt Amentioning
confidence: 99%
“…While the quantity of this 5-HT paled compared with the 5-HT made by the intestine, it is an important finding because it draws attention to two points. Part of the reason for pursuing 5-HT as a pathogenic factor in hypertension is that plasma levels of 5-HT are elevated in hypertension subjects compared with subjects with normal blood pressure (5,13). One could envision this higher level of 5-HT activating vascular receptors to promote increases in total peripheral resistance and blood pressure.…”
Section: Where Does the 5-ht Come From?mentioning
confidence: 99%